2012
DOI: 10.2527/jas.2011-4278
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem titin proteolysis is influenced by sarcomere length in bovine muscle1

Abstract: The calpain protease system, in particular, μ-calpain is involved in the disassembly of specific myofibrillar proteins, resulting in tenderization of meat postmortem. Given the size, complexity, and integral nature of titin to the structure of the sarcomere, it is plausible that the length of a sarcomere may alter the susceptibility of various domains of titin to cleavage by the calpains. Therefore, we hypothesized titin degradation differs in a sarcomere-length-dependent manner in beef. After slaughter, beef … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…() muscles with longer sarcomere lengths have lower resistance of shear force (more tender) and are more susceptible to post mortem proteolysis (England et al . ). The effect of slaughter methods on sarcomere length in LL muscle is shown in Figure .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…() muscles with longer sarcomere lengths have lower resistance of shear force (more tender) and are more susceptible to post mortem proteolysis (England et al . ). The effect of slaughter methods on sarcomere length in LL muscle is shown in Figure .…”
Section: Resultsmentioning
confidence: 97%
“…It is a good indicator of tenderization due to its close relationship with meat tenderness (Kandeepan et al 2009). According to Weaver et al (2008) muscles with longer sarcomere lengths have lower resistance of shear force (more tender) and are more susceptible to post mortem proteolysis (England et al 2012). The effect of slaughter methods on sarcomere length in LL muscle is shown in Figure 1.…”
Section: Sarcomere Lengthmentioning
confidence: 99%
“…On muscle fibre, sarcomeres are bounded by two successive Z-lines, where fine filaments are anchored and thick filaments are located in the middle (Sabow et al, 2015). Sarcomere length is related to meat tenderness as muscles with longer sarcomeres are less resistant to shear force (these meat products are softer) (Weaver et al, 2008) and are more susceptible to post-mortem proteolysis (England et al, 2012). Therefore, it can be inferred that stress induced by anoxia for 3 and 6 min in Nile tilapias produces fillets with a less firm texture.…”
Section: Discussionmentioning
confidence: 99%
“…Wheeler and Koohmaraie (1999) reported a range in sarcomere lengths from 1.36 μm (cold-shortened longissimus) to 1.69 μm (normal longissimus). Similar results were found by King et al (2003) and England et al (2012) who reported post-mortem sarcomere lengths of 1.78 μm and 1.82 μm in bovine longissimus, respectively. Furthermore, many studies on feeding distillers grains reported no differences in sarcomere length (OLTRA et al, 2008.…”
Section: Sarcomere Lengthsupporting
confidence: 89%